2013
DOI: 10.1016/j.lungcan.2013.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Impact of renal function on treatment options and outcomes in advanced non-small cell lung cancer

Abstract: Introduction Certain chemotherapeutic agents commonly used for advanced non-small cell lung cancer (NSCLC) require minimum threshold renal function for administration. To determine how such requirements affect treatment options, we evaluated renal function patterns in this population. Methods We performed a single-center retrospective analysis of patients treated for stage IV NSCLC from 2000 to 2007. Associations between patient characteristics, calculated creatinine clearance (CrCl), and clinical outcomes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…Cockcroft–Gault formula [15] was selected for the determination renal function status because it is the most commonly used formula in the clinical care of cancer patients. The correlation to measured CrCl in multiple disease settings had been proven [16] . Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) [17] developed a new formulation to estimates renal function.…”
Section: Methodsmentioning
confidence: 99%
“…Cockcroft–Gault formula [15] was selected for the determination renal function status because it is the most commonly used formula in the clinical care of cancer patients. The correlation to measured CrCl in multiple disease settings had been proven [16] . Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) [17] developed a new formulation to estimates renal function.…”
Section: Methodsmentioning
confidence: 99%
“…Over 80% of protocols in our analysis mandated adequate kidney function, commonly defined as a creatinine clearance ≥ 60 mL/min—a threshold that over 20% of lung cancer patients fall below at some point during their treatment history. 31 Accordingly, such restrictions might be limited to trials of therapies cleared renally or conveying renal toxicity. These observations echo those from other fields, including a recent analysis of hematologic malignancy protocols which found that most eligibility criteria did not correlate with known, observed adverse events of study therapy.…”
Section: Discussionmentioning
confidence: 99%
“…CKD staging was conducted in accordance with the current international guidelines . The Cockcroft–Gault formula, the most commonly used formula to determine renal function status in the clinical care of cancer patients, has been shown to correlate with measured CrCl in multiple disease settings . A recent formulation to estimate renal function was developed by the Chronic Kidney Disease Epidemiology Collaboration (CKD‐EPI) .…”
Section: Methodsmentioning
confidence: 99%